The Correlation between Akidah Akhlak Learning Outcomes and Muslimah Dress Code Outside School - Opi Qurotul Aini; Fathurohim Fathurohim; Pipit Muliyah (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: The Correlation between Akidah Akhlak Learning Outcomes and Muslimah Dress Code Outside SchoolNowadays, fashion trends have developed rapidly by bringing up various clothing models that affect the ethics of Muslim women's dress. This study aims to determine whether there is a relationship between the learning outcomes of akidah akhlak and the ethics of Muslim women's dress outside school for class XII students. This research is a type of field research with a quantitative approach with sampling using a random sampling technique of as many as 75 class XII students. Data collection techniques in this study used observation techniques, interviews, documentation, and questionnaires (questionnaires). The analysis technique in this study used the Spearman Rank Correlation technique using the IBM SPSS 25 statistical operating system. The results of this study indicate that the value of the correlation coefficient between the learning outcomes of akidah akhlak and the ethics of dressing Muslim women outside school is 0.270 with rtable 0.227 which indicates that Ha is accepted and H0 is rejected and included in the strength of the low correlation relationship. With a significance level value of 0.019 <0.05. This means that there is a relationship between the results of learning akidah akhlak and the ethics of dressing Muslim women outside the school with a positive or unidirectional correlation direction.Abstract: Hubungan antara Hasil Belajar Akidah Akhlak dengan Etika Berbusana Muslimah di Luar SekolahDewasa ini, tren fashion telah berkembang pesat dengan memunculkan model pakaian yang beragam hingga mempengaruhi etika berbusana wanita muslimah. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara hasil belajar akidah akhlak dengan etika berbusana muslimah di luar sekolah siswa kelas XII. Penelitian ini merupakan jenis field research dengan pendekatan kuantitatif dengan pengambilan sampel menggunakan teknik sample random sampling sebanyak 75 siswa kelas XII. Teknik pengumpulan data pada penelitian ini menggunakan teknik observasi, wawancara, dokumentasi, dan kuesioner (angket). Teknik analisis pada penelitian ini menggunakan teknik Korelasi Spearman Rank dengan menggunakan system operasi statistic IBM SPSS 25. Hasil penelitian ini menunjukan bahwa nilai koefisien korelasi antara hasil belajar akidah akhlak dengan etika berbusana muslimah di luar sekolah sebesar 0,270 dengan rtabel 0,227 yang menunjukan bahwa Ha diterima dan H0 ditolak dan termasuk dalam kekuatan hubungan korelasi rendah. Dengan nilai taraf signifikasi 0,019 < 0,05. Yang berarti terdapat hubungan antara hasil belajar akidah akhlak dengan etika berbusana muslimah di luar sekolah dengan arah korelasi positif atau searah.